Low-temperature fast curing solder formula and preparation method thereof
By using a combination formula of multi-alloy matrix powder, particle dopant, anhydrous ethanol and flux, low temperature rapid curing solder is prepared, which solves the problems of existing solder high curing temperature, low welding efficiency and poor adaptability, and achieves efficient, fast and highly adaptable welding effects.
Patent Information
- Application Number
- CN202510033856.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing solder has high curing temperature, low welding efficiency and poor adaptability, which can easily cause thermal damage to the thermally sensitive components and a long welding time, resulting in a reduced production line speed.
The combination formula of multi-alloy matrix powder, particle dopants, anhydrous ethanol and flux is used to prepare low-temperature rapid curing solder through high-energy ball milling and vacuum stirring.
It achieves rapid curing at lower temperatures, reduces the risk of thermal damage to the thermal-sensitive components, improves welding efficiency and adaptability, and ensures welding joint quality and production line speed.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of welding materials, and more particularly to a low-temperature fast-curing solder formula and a preparation method thereof. Background Art
[0002] In many fields such as electronic manufacturing and precision instrument assembly, welding is a key connection process. During the welding process, the solder is heated and melted, then it infiltrates the base material, fills the joint gap, and diffuses with the base material to achieve a welding connection. It has the characteristics of high mechanical strength and good electrical conductivity, and can meet the needs of various engineering applications. Therefore, the development of a new solder has important practical significance.
[0003] The solder in the relevant technology mainly includes lead and tin; among them, lead has good fluidity, which can enable the solder to better fill the weld during the welding process and help the solder to spread smoothly on the surface of the weldment, thereby achieving the purpose of connecting parts; and lead can lower the melting point of the solder, so that the welding operation can be carried out at a relatively low temperature, reducing the thermal shock to the welded components; tin is also a key component of solder, which can provide a certain mechanical strength, ensure the firmness of the welding part, enable the solder joint to withstand a certain external force, maintain the connection stability of electronic components, etc., and ensure the normal conduction of the circuit.
[0004] However, it still has some disadvantages in actual use, such as high curing temperature. The melting point of the solder in the related technology is relatively high. When welding thermistors, this high curing temperature can easily cause thermal damage to the components; low welding efficiency; the solder in the related technology needs to reach a higher temperature to melt during the welding process, and it may take a certain amount of time after melting to ensure good wettability and filling effect, so the welding time is relatively long; a longer residence time is required on the solder joint to ensure the quality of the solder joint, which will reduce the speed of the welding production line; poor adaptability. The wettability of the solder in the related technology on some special welding surfaces is not ideal. This is because its composition and performance are relatively fixed, and it cannot adapt well to various complex welding surfaces, resulting in poor quality of solder joints and welding defects such as cold solder joints and sharp tips. Summary of the invention
[0005] In order to improve the above problems and reduce the problems of high solder curing temperature, low welding efficiency and low welding efficiency in the related art, the present invention specially provides a low-temperature fast-curing solder formula and a preparation method thereof to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions: A low-temperature fast-curing solder comprises a multi-element alloy matrix powder, a particle dopant, anhydrous ethanol and a soldering flux; and a preparation method thereof comprises the following steps: A1. Put the multi-element alloy matrix powder and the particle dopant into a high-energy ball mill, then add anhydrous ethanol, and ball mill at a speed of 350-450 r / min for 3-5 hours to obtain a mixed material; A2. Transfer the mixture obtained in A1 into a vacuum mixer and stir at a vacuum degree of 10-3Pa. The mixture was mixed at 200-300 r / min for 2-3 hours, during which time the flux was added dropwise at a dropwise acceleration rate of 2-4 mL / min; a low-temperature fast-curing solder was obtained.
[0007] Preferably, the raw material components and weight proportions of the low-temperature rapid solidification solder are as follows: 55-62 parts of multi-element alloy matrix powder, 10-15 parts of particle dopant, 3-4 parts of anhydrous ethanol and 18-22 parts of flux.
[0008] Preferably, the multi-element alloy matrix powder is prepared from tin, bismuth, indium and gallium.
[0009] Preferably, the method for preparing the multi-element alloy matrix powder comprises the following steps: C1. Place 99% pure tin, bismuth, indium and gallium metal blocks into a vacuum induction melting furnace at a vacuum degree of 10 -5 -10 -4 Pa, smelting at 1100-1300℃ for 30-45min to obtain multi-element alloy liquid; C2, placing the multi-component alloy liquid obtained in C1 in the atomizing chamber of an ultrasonic atomizing device, atomizing the alloy liquid into tiny droplets at an ultrasonic frequency of 20-30kHz and an atomizing gas argon flow rate of 12-18L / min, cooling and solidifying the droplets through circulating water at a temperature of 10°C and a flow rate of 0.5L / min during the drop, to obtain a multi-component alloy powder; C3. The multi-component alloy powder obtained in C2 is transferred to an air flow classifier, and air flow classification is performed under the conditions of a classifying wheel speed of 1500-2000 r / min, an air flow rate of 8 m³ / h, and an air flow pressure maintained at 0.2 MPa to obtain a multi-component alloy matrix powder.
[0010] Preferably, the components and weight proportions of the raw materials for preparing the multi-element alloy matrix powder are as follows: 3.5-5.5 parts of tin, 2.5-4 parts of bismuth, 0.8-1.5 parts of indium and 0.8-1.5 parts of gallium.
[0011] Preferably, the particle dopant is prepared from cerium-doped particles, silver-doped particles and carbon-doped dispersion.
[0012] Preferably, the method for preparing the particle dopant comprises the following steps: B1. Dissolve cerium nitrate in 4 times the volume of ethylene glycol solution, then add polyvinyl pyrrolidone and continue stirring for 30 minutes, then place in a high-pressure reactor, react at a temperature of 180-200°C for 4-6 hours. After the reaction is completed, wait for the high-pressure reactor to cool naturally to room temperature, transfer the generated precipitate to a centrifuge tube, centrifuge at a speed of 8000r / min for 15 minutes, take the precipitate, then add anhydrous ethanol to the precipitate, use an oscillator to oscillate for 5 minutes, and then centrifuge again under the same conditions. Repeat 3 times and heat at a temperature of 60°C and a vacuum degree of 10 -4 The cerium-doped particles were obtained by drying under Pa conditions for 12 h; B2. Add 5 times the volume of glucose solution to the silver nitrate solution, stir at 300-400 r / min, 80-100°C for 2-3 h, then transfer the product to a centrifuge tube, add 5 times the volume of anhydrous ethanol, oscillate for 5 min, then centrifuge at 8000 r / min for 10 min, remove the supernatant, repeat 3 times, and heat at 60°C in a vacuum for 10 min. - 4 Drying under Pa conditions for 12 h yields silver-doped particles; B3, adding carbon nanotubes to sodium dodecyl sulfate, then placing in 10 times the volume of water, ultrasonically oscillating at an ultrasonic frequency of 40-60 Hz for 30-45 minutes, taking out the dispersion to obtain a carbon-doped dispersion; B4, the cerium-doped particles obtained in B1, the silver-doped particles obtained in B2, and the carbon-doped dispersion obtained in B3 were mixed, and then placed in 1 volume of anhydrous ethanol, followed by ultrasonic cleaning at a frequency of 30 Hz for 10 min, and then vacuumed to 10 -4 Pa, and dried at 60°C for 6h to obtain a particle dopant.
[0013] Preferably, the components and weight proportions of the raw materials for preparing the particle dopant are as follows: 2-4 parts of cerium-doped particles, 2-5 parts of silver-doped particles and 3-4 parts of carbon-doped dispersion.
[0014] Preferably, the soldering flux is composed of a thermosensitive polymer, an amphiphilic active agent, a free radical scavenger and a bio-based lubricant in a weight ratio of (8-10): (4-6): (2-3): (1-2).
[0015] Preferably, the mass ratio of cerium nitrate to polyvinyl pyrrolidone in B1 is (5-10): 1; The molar ratio of silver nitrate to glucose in B2 is 1:(1-1.5); The mass ratio of carbon nanotubes to sodium dodecyl sulfate in B3 is 1:(0.08-0.12).
[0016] Technical effects and advantages of the present invention: The present invention adds bismuth elements during the preparation process. In the alloy system, bismuth atoms interact with other metal atoms, changing the overall crystallization behavior of the alloy, so that the alloy can start the solidification process at a relatively low temperature, laying a foundation for low-temperature solidification, and can achieve solidification at a relatively low temperature, which can effectively avoid thermal damage to thermistors, and is more suitable for welding operations in a low-temperature environment, reducing the dependence on complex heating equipment; The invention adds cerium-doped particles during the preparation process, so that the invention can complete the curing process within a few seconds at a relatively low temperature. This fast curing feature greatly improves welding efficiency, can improve production efficiency, and reduce production cycles; The invention contains a variety of functional components, which can make the solder spread better on the welding surface and can adapt to more types of welding surfaces, including some new materials with higher wettability requirements, thereby improving the quality of solder joints and ensuring the reliability of welding. DETAILED DESCRIPTION
[0017] The present invention is further described in detail below in conjunction with the embodiments of the present invention. The raw materials used in the examples and embodiments of the present invention are all commercially available common materials unless otherwise specified below. Preparation Example 1-5 A multi-element alloy matrix powder, the preparation components and their corresponding proportions are shown in the following table, and is prepared by the following preparation method: C1. Place 99% pure tin, bismuth, indium and gallium metal blocks into a vacuum induction melting furnace at a vacuum degree of 10 -5 Pa, smelting at 1100°C for 30 min to obtain a multi-element alloy liquid; C2, placing the multi-component alloy liquid obtained in C1 in the atomizing chamber of an ultrasonic atomizing device, atomizing the alloy liquid into tiny droplets at an ultrasonic frequency of 20 kHz and an atomizing gas argon flow rate of 12 L / min, cooling and solidifying the droplets in circulating water at a temperature of 10° C. and a flow rate of 0.5 L / min during the drop, to obtain a multi-component alloy powder; C3. The multi-component alloy powder obtained in C2 is transferred to an air flow classifier, and air flow classification is performed under the conditions of a classifying wheel speed of 1500 r / min, an air flow rate of 8 m³ / h, and an air flow pressure maintained at 0.2 MPa to obtain a multi-component alloy matrix powder.
[0018] Table: Components and mass ratios of raw materials in Preparation Examples 1-5 (kg)
[0019] Preparation Example 6 A multi-element alloy matrix powder, which is different from Preparation Example 1 in that the preparation method is as follows: C1. Place 99% pure tin, bismuth, indium and gallium metal blocks into a vacuum induction melting furnace at a vacuum degree of 10 -5 Pa, smelting at 1200℃ for 35min to obtain multi-element alloy liquid; C2, placing the multi-component alloy liquid obtained in C1 in the atomizing chamber of an ultrasonic atomizing device, atomizing the alloy liquid into tiny droplets at an ultrasonic frequency of 20 kHz and an atomizing gas argon flow rate of 12 L / min, cooling and solidifying the droplets in circulating water at a temperature of 10° C. and a flow rate of 0.5 L / min during the drop, to obtain a multi-component alloy powder; C3. The multi-component alloy powder obtained in C2 is transferred to an air flow classifier, and air flow classification is performed under the conditions of a classifying wheel speed of 1500 r / min, an air flow rate of 8 m³ / h, and an air flow pressure maintained at 0.2 MPa to obtain a multi-component alloy matrix powder.
[0020] Preparation Example 7 A multi-element alloy matrix powder, which is different from Preparation Example 1 in that the preparation method is as follows: C1. Place 99% pure tin, bismuth, indium and gallium metal blocks into a vacuum induction melting furnace at a vacuum degree of 10 -4 Pa, smelting at 1200℃ for 40min to obtain multi-element alloy liquid; C2, placing the multi-component alloy liquid obtained in C1 in the atomizing chamber of an ultrasonic atomizing device, atomizing the alloy liquid into tiny droplets at an ultrasonic frequency of 20 kHz and an atomizing gas argon flow rate of 12 L / min, cooling and solidifying the droplets in circulating water at a temperature of 10° C. and a flow rate of 0.5 L / min during the drop, to obtain a multi-component alloy powder; C3. The multi-component alloy powder obtained in C2 is transferred to an air flow classifier, and air flow classification is performed under the conditions of a classifying wheel speed of 1500 r / min, an air flow rate of 8 m³ / h, and an air flow pressure maintained at 0.2 MPa to obtain a multi-component alloy matrix powder.
[0021] Preparation Example 8 A multi-element alloy matrix powder, which is different from Preparation Example 1 in that the preparation method is as follows: C1. Place 99% pure tin, bismuth, indium and gallium metal blocks into a vacuum induction melting furnace at a vacuum degree of 10 -4 Pa, smelting at 1300℃ for 45min to obtain multi-element alloy liquid; C2, placing the multi-component alloy liquid obtained in C1 in the atomizing chamber of an ultrasonic atomizing device, atomizing the alloy liquid into tiny droplets at an ultrasonic frequency of 20 kHz and an atomizing gas argon flow rate of 12 L / min, cooling and solidifying the droplets in circulating water at a temperature of 10° C. and a flow rate of 0.5 L / min during the drop, to obtain a multi-component alloy powder; C3. The multi-component alloy powder obtained in C2 is transferred to an air flow classifier, and air flow classification is performed under the conditions of a classifying wheel speed of 1500 r / min, an air flow rate of 8 m³ / h, and an air flow pressure maintained at 0.2 MPa to obtain a multi-component alloy matrix powder.
[0022] Preparation Example 9 A multi-element alloy matrix powder, which is different from Preparation Example 1 in that the preparation method is as follows: C1. Place 99% pure tin, bismuth, indium and gallium metal blocks into a vacuum induction melting furnace at a vacuum degree of 10 -5 Pa, smelting at 1100°C for 30 min to obtain a multi-element alloy liquid; C2, placing the multi-component alloy liquid obtained in C1 in the atomizing chamber of an ultrasonic atomizing device, atomizing the alloy liquid into tiny droplets at an ultrasonic frequency of 25 kHz and an atomizing gas argon flow rate of 15 L / min, cooling and solidifying the droplets in circulating water at a temperature of 10° C. and a flow rate of 0.5 L / min during the drop, to obtain a multi-component alloy powder; C3. The multi-component alloy powder obtained in C2 is transferred to an air flow classifier, and air flow classification is performed under the conditions of a classifying wheel speed of 1500 r / min, an air flow rate of 8 m³ / h, and an air flow pressure maintained at 0.2 MPa to obtain a multi-component alloy matrix powder.
[0023] Preparation Example 10 A multi-element alloy matrix powder, which is different from Preparation Example 1 in that the preparation method is as follows: C1. Place 99% pure tin, bismuth, indium and gallium metal blocks into a vacuum induction melting furnace at a vacuum degree of 10 -5 Pa, smelting at 1100°C for 30 min to obtain a multi-element alloy liquid; C2, placing the multi-component alloy liquid obtained in C1 in the atomizing chamber of an ultrasonic atomizing device, atomizing the alloy liquid into tiny droplets at an ultrasonic frequency of 30 kHz and an atomizing gas argon flow rate of 18 L / min, cooling and solidifying the droplets in circulating water at a temperature of 10° C. and a flow rate of 0.5 L / min during the drop, to obtain a multi-component alloy powder; C3. The multi-component alloy powder obtained in C2 is transferred to an air flow classifier, and air flow classification is performed under the conditions of a classifying wheel speed of 1500 r / min, an air flow rate of 8 m³ / h, and an air flow pressure maintained at 0.2 MPa to obtain a multi-component alloy matrix powder.
[0024] Preparation Example 11 A multi-element alloy matrix powder, which is different from Preparation Example 1 in that the preparation method is as follows: C1. Place 99% pure tin, bismuth, indium and gallium metal blocks into a vacuum induction melting furnace at a vacuum degree of 10 -5Pa, smelting at 1100°C for 30 min to obtain a multi-element alloy liquid; C2, placing the multi-component alloy liquid obtained in C1 in the atomizing chamber of an ultrasonic atomizing device, atomizing the alloy liquid into tiny droplets at an ultrasonic frequency of 20 kHz and an atomizing gas argon flow rate of 12 L / min, cooling and solidifying the droplets in circulating water at a temperature of 10° C. and a flow rate of 0.5 L / min during the drop, to obtain a multi-component alloy powder; C3. The multi-component alloy powder obtained in C2 is transferred to an air flow classifier, and air flow classification is performed under the conditions of a classifying wheel speed of 1750 r / min, an air flow rate of 8 m³ / h, and an air flow pressure maintained at 0.2 MPa to obtain a multi-component alloy matrix powder.
[0025] Preparation Example 12 A multi-element alloy matrix powder, which is different from Preparation Example 1 in that the preparation method is as follows: C1. Place 99% pure tin, bismuth, indium and gallium metal blocks into a vacuum induction melting furnace at a vacuum degree of 10 -5 Pa, smelting at 1100°C for 30 min to obtain a multi-element alloy liquid; C2, placing the multi-component alloy liquid obtained in C1 in the atomizing chamber of an ultrasonic atomizing device, atomizing the alloy liquid into tiny droplets at an ultrasonic frequency of 20 kHz and an atomizing gas argon flow rate of 12 L / min, cooling and solidifying the droplets in circulating water at a temperature of 10° C. and a flow rate of 0.5 L / min during the drop, to obtain a multi-component alloy powder; C3. The multi-component alloy powder obtained in C2 is transferred to an air flow classifier, and air flow classification is performed under the conditions of a classifying wheel speed of 2000 r / min, an air flow rate of 8 m³ / h, and an air flow pressure maintained at 0.2 MPa to obtain a multi-component alloy matrix powder.
[0026] Preparation Examples 13-17 A particle dopant, the preparation components and their corresponding proportions are shown in the following table, and the particle dopant is prepared by the following preparation method: B1. Dissolve cerium nitrate in 4 times the volume of ethylene glycol solution, then add polyvinyl pyrrolidone and continue stirring for 30 minutes, then place in a high-pressure reactor, react at a temperature of 180°C for 4 hours. After the reaction is completed, wait for the high-pressure reactor to cool naturally to room temperature, transfer the generated precipitate to a centrifuge tube, centrifuge at a speed of 8000r / min for 15 minutes, take the precipitate, then add anhydrous ethanol to the precipitate, use an oscillator to oscillate for 5 minutes, and then centrifuge again under the same conditions. Repeat 3 times and heat at a temperature of 60°C and a vacuum degree of 10 -4 The cerium-doped particles were obtained by drying under Pa conditions for 12 h; The mass ratio of cerium nitrate to polyvinyl pyrrolidone is 10:1; B2. Add 5 times the volume of glucose solution to the silver nitrate solution, stir at 300 r / min, 80°C for 2 h, then transfer the product to a centrifuge tube, add 5 times the volume of anhydrous ethanol, oscillate for 5 min, then centrifuge at 8000 r / min for 10 min, remove the supernatant, repeat 3 times, and heat at 60°C in a vacuum for 10 min. -4 Drying under Pa conditions for 12 h yields silver-doped particles; The molar ratio of silver nitrate to glucose is 1:1; B3, adding carbon nanotubes to sodium dodecyl sulfate, then placing in 10 times the volume of water, ultrasonically oscillating at an ultrasonic frequency of 40 Hz for 30 minutes, taking out the dispersion to obtain a carbon-doped dispersion; The mass ratio of carbon nanotubes to sodium dodecyl sulfate is 1:0.08; B4, the cerium-doped particles obtained in B1, the silver-doped particles obtained in B2, and the carbon-doped dispersion obtained in B3 were mixed, and then placed in 1 volume of anhydrous ethanol, followed by ultrasonic cleaning at a frequency of 30 Hz for 10 min, and then vacuumed to 10 -4 Pa, and dried at 60°C for 6h to obtain a particle dopant.
[0027] Table: Components and mass ratios of raw materials in Preparation Examples 13-17 (kg)
[0028] Preparation Example 18 A particle dopant, which is different from Preparation Example 13 in that the preparation method is as follows: B1. Dissolve cerium nitrate in 4 times the volume of ethylene glycol solution, then add polyvinyl pyrrolidone and continue stirring for 30 minutes, then place in a high-pressure reactor, react at a temperature of 190°C for 5 hours, after the reaction is completed, wait for the high-pressure reactor to cool naturally to room temperature, transfer the generated precipitate to a centrifuge tube, centrifuge at a speed of 8000r / min for 15 minutes, take the precipitate, then add anhydrous ethanol to the precipitate, use an oscillator to shake for 5 minutes, and then centrifuge again under the same conditions, repeat 3 times, and heat at a temperature of 60°C and a vacuum degree of 10 -4 The cerium-doped particles were obtained by drying under Pa conditions for 12 h; B2. Add 5 times the volume of glucose solution to the silver nitrate solution, react at a stirring speed of 300 r / min and a temperature of 80°C for 2 h, then transfer the product to a centrifuge tube, add 5 times the volume of anhydrous ethanol, oscillate on an oscillator for 5 min, and then centrifuge at 8000 r / min for 10 min, remove the supernatant, repeat 3 times, and dry at a temperature of 60°C and a vacuum degree of 10-4 Pa for 12 h to obtain silver-doped particles; B3, adding carbon nanotubes to sodium dodecyl sulfate, then placing in 10 times the volume of water, ultrasonically oscillating at an ultrasonic frequency of 40 Hz for 30 minutes, taking out the dispersion to obtain a carbon-doped dispersion; B4, the cerium-doped particles obtained in B1, the silver-doped particles obtained in B2, and the carbon-doped dispersion obtained in B3 were mixed, and then placed in 1 volume of anhydrous ethanol, followed by ultrasonic cleaning at a frequency of 30 Hz for 10 min, and then vacuumed to 10 -4 Pa, and dried at 60°C for 6h to obtain a particle dopant.
[0029] Preparation Example 19 A particle dopant, which is different from Preparation Example 13 in that the preparation method is as follows: B1. Dissolve cerium nitrate in 4 times the volume of ethylene glycol solution, then add polyvinyl pyrrolidone and continue stirring for 30 minutes, then place in a high-pressure reactor, react at a temperature of 1000°C for 6 hours. After the reaction is completed, wait for the high-pressure reactor to cool naturally to room temperature, transfer the generated precipitate to a centrifuge tube, centrifuge at a speed of 8000r / min for 15 minutes, take the precipitate, then add anhydrous ethanol to the precipitate, use an oscillator to oscillate for 5 minutes, and then centrifuge again under the same conditions. Repeat 3 times and heat at a temperature of 60°C and a vacuum degree of 10 -4 The cerium-doped particles were obtained by drying under Pa conditions for 12 h; B2. Add 5 times the volume of glucose solution to the silver nitrate solution, stir at 300 r / min, 80°C for 2 h, then transfer the product to a centrifuge tube, add 5 times the volume of anhydrous ethanol, oscillate for 5 min, then centrifuge at 8000 r / min for 10 min, remove the supernatant, repeat 3 times, and heat at 60°C in a vacuum for 10 min. -4 Drying under Pa conditions for 12 h yields silver-doped particles; B3, adding carbon nanotubes to sodium dodecyl sulfate, then placing in 10 times the volume of water, ultrasonically oscillating at an ultrasonic frequency of 40 Hz for 30 minutes, taking out the dispersion to obtain a carbon-doped dispersion; B4, the cerium-doped particles obtained in B1, the silver-doped particles obtained in B2, and the carbon-doped dispersion obtained in B3 were mixed, and then placed in 1 volume of anhydrous ethanol, followed by ultrasonic cleaning at a frequency of 30 Hz for 10 min, and then vacuumed to 10 -4 Pa, and dried at 60°C for 6h to obtain a particle dopant.
[0030] Preparation Example 20 A particle dopant, which is different from Preparation Example 13 in that the preparation method is as follows: B1. Dissolve cerium nitrate in 4 times the volume of ethylene glycol solution, then add polyvinyl pyrrolidone and continue stirring for 30 minutes, then place in a high-pressure reactor, react at a temperature of 180°C for 4 hours. After the reaction is completed, wait for the high-pressure reactor to cool naturally to room temperature, transfer the generated precipitate to a centrifuge tube, centrifuge at a speed of 8000r / min for 15 minutes, take the precipitate, then add anhydrous ethanol to the precipitate, use an oscillator to oscillate for 5 minutes, and then centrifuge again under the same conditions. Repeat 3 times and heat at a temperature of 60°C and a vacuum degree of 10 -4 The cerium-doped particles were obtained by drying under Pa conditions for 12 h; B2. Add 5 times the volume of glucose solution to the silver nitrate solution, stir at 350 r / min, 90°C for 2.5 h, then transfer the product to a centrifuge tube, add 5 times the volume of anhydrous ethanol, oscillate for 5 min, then centrifuge at 8000 r / min for 10 min, remove the supernatant, repeat 3 times, and heat at 60°C in a vacuum for 10 min. -4 Drying under Pa conditions for 12 h yields silver-doped particles; B3, adding carbon nanotubes to sodium dodecyl sulfate, then placing in 10 times the volume of water, ultrasonically oscillating at an ultrasonic frequency of 40 Hz for 30 minutes, taking out the dispersion to obtain a carbon-doped dispersion; B4, the cerium-doped particles obtained in B1, the silver-doped particles obtained in B2, and the carbon-doped dispersion obtained in B3 were mixed, and then placed in 1 volume of anhydrous ethanol, followed by ultrasonic cleaning at a frequency of 30 Hz for 10 min, and then vacuumed to 10 -4 Pa, and dried at 60°C for 6h to obtain a particle dopant.
[0031] Preparation Example 21 A particle dopant, which is different from Preparation Example 13 in that the preparation method is as follows: B1. Dissolve cerium nitrate in 4 times the volume of ethylene glycol solution, then add polyvinyl pyrrolidone and continue stirring for 30 minutes, then place in a high-pressure reactor, react at a temperature of 180°C for 4 hours. After the reaction is completed, wait for the high-pressure reactor to cool naturally to room temperature, transfer the generated precipitate to a centrifuge tube, centrifuge at a speed of 8000r / min for 15 minutes, take the precipitate, then add anhydrous ethanol to the precipitate, use an oscillator to oscillate for 5 minutes, and then centrifuge again under the same conditions. Repeat 3 times and heat at a temperature of 60°C and a vacuum degree of 10 -4 The cerium-doped particles were obtained by drying under Pa conditions for 12 h; B2. Add 5 times the volume of glucose solution to the silver nitrate solution, stir at 400 r / min, 100°C for 3 h, then transfer the product to a centrifuge tube, add 5 times the volume of anhydrous ethanol, oscillate for 5 min, then centrifuge at 8000 r / min for 10 min, remove the supernatant, repeat 3 times, and heat at 60°C in a vacuum for 10 min. -4 Drying under Pa conditions for 12 h yields silver-doped particles; B3, adding carbon nanotubes to sodium dodecyl sulfate, then placing in 10 times the volume of water, ultrasonically oscillating at an ultrasonic frequency of 40 Hz for 30 minutes, taking out the dispersion to obtain a carbon-doped dispersion; B4, the cerium-doped particles obtained in B1, the silver-doped particles obtained in B2, and the carbon-doped dispersion obtained in B3 were mixed, and then placed in 1 volume of anhydrous ethanol, followed by ultrasonic cleaning at a frequency of 30 Hz for 10 min, and then vacuumed to 10 -4 Pa, and dried at 60°C for 6 hours to obtain a particle dopant.
[0032] Preparation Example 22 A particle dopant, which is different from Preparation Example 13 in that the preparation method is as follows: B1. Dissolve cerium nitrate in 4 times the volume of ethylene glycol solution, then add polyvinyl pyrrolidone and continue stirring for 30 minutes, then place in a high-pressure reactor, react at a temperature of 180°C for 4 hours. After the reaction is completed, wait for the high-pressure reactor to cool naturally to room temperature, transfer the generated precipitate to a centrifuge tube, centrifuge at a speed of 8000r / min for 15 minutes, take the precipitate, then add anhydrous ethanol to the precipitate, use an oscillator to oscillate for 5 minutes, and then centrifuge again under the same conditions. Repeat 3 times and heat at a temperature of 60°C and a vacuum degree of 10 -4 The cerium-doped particles were obtained by drying under Pa conditions for 12 h; B2. Add 5 times the volume of glucose solution to the silver nitrate solution, stir at 300 r / min, 80°C for 2 h, then transfer the product to a centrifuge tube, add 5 times the volume of anhydrous ethanol, oscillate for 5 min, then centrifuge at 8000 r / min for 10 min, remove the supernatant, repeat 3 times, and heat at 60°C in a vacuum for 10 min. -4 Drying under Pa conditions for 12 h yields silver-doped particles; B3, adding carbon nanotubes to sodium dodecyl sulfate, then placing in 10 times the volume of water, ultrasonically oscillating at an ultrasonic frequency of 50 Hz for 40 minutes, taking out the dispersion to obtain a carbon-doped dispersion; B4, the cerium-doped particles obtained in B1, the silver-doped particles obtained in B2, and the carbon-doped dispersion obtained in B3 were mixed, and then placed in 1 volume of anhydrous ethanol, followed by ultrasonic cleaning at a frequency of 30 Hz for 10 min, and then vacuumed to 10 -4 Pa, and dried at 60°C for 6 hours to obtain a particle dopant.
[0033] Preparation Example 23 A particle dopant, which is different from Preparation Example 13 in that the preparation method is as follows: B1. Dissolve cerium nitrate in 4 times the volume of ethylene glycol solution, then add polyvinyl pyrrolidone and continue stirring for 30 minutes, then place in a high-pressure reactor, react at a temperature of 180°C for 4 hours. After the reaction is completed, wait for the high-pressure reactor to cool naturally to room temperature, transfer the generated precipitate to a centrifuge tube, centrifuge at a speed of 8000r / min for 15 minutes, take the precipitate, then add anhydrous ethanol to the precipitate, use an oscillator to oscillate for 5 minutes, and then centrifuge again under the same conditions. Repeat 3 times and heat at a temperature of 60°C and a vacuum degree of 10 -4 The cerium-doped particles were obtained by drying under Pa conditions for 12 h; B2. Add 5 times the volume of glucose solution to the silver nitrate solution, stir at 300 r / min, 80°C for 2 h, then transfer the product to a centrifuge tube, add 5 times the volume of anhydrous ethanol, oscillate for 5 min, then centrifuge at 8000 r / min for 10 min, remove the supernatant, repeat 3 times, and heat at 60°C in a vacuum for 10 min. -4 Drying under Pa conditions for 12 h yields silver-doped particles; B3, adding carbon nanotubes to sodium dodecyl sulfate, then placing in 10 times volume of water, ultrasonically oscillating at an ultrasonic frequency of 60 Hz for 45 minutes, taking out the dispersion to obtain a carbon-doped dispersion; B4, the cerium-doped particles obtained in B1, the silver-doped particles obtained in B2, and the carbon-doped dispersion obtained in B3 were mixed, and then placed in 1 volume of anhydrous ethanol, followed by ultrasonic cleaning at a frequency of 30 Hz for 10 min, and then vacuumed to 10 -4 Pa, and dried at 60°C for 6 hours to obtain a particle dopant.
[0034] Preparation Example 24 A particle dopant, which is different from Preparation Example 13 in that the mass ratio of cerium nitrate to polyvinyl pyrrolidone in B1 is 5:1.
[0035] Preparation Example 25 A particle dopant, which is different from Preparation Example 13 in that the molar ratio of silver nitrate to glucose in B2 is 1:1.5.
[0036] Preparation Example 26 A particle dopant, which is different from Preparation Example 13 in that the mass ratio of carbon nanotubes to sodium dodecyl sulfate in B3 is 1:0.12.
[0037] Preparation Examples 27-31 A low temperature fast curing solder, the preparation components and their corresponding proportions are shown in the following table, and is prepared by the following preparation method: A1. Put the multi-element alloy matrix powder and the particle dopant into a high-energy ball mill, then add anhydrous ethanol, and ball mill at a speed of 350 r / min for 3 hours to obtain a mixed material; The multi-element alloy matrix powder is prepared by Preparation Example 1; The particle dopant was prepared by Preparation Example 13; A2: Transfer the mixture obtained in A1 into a vacuum mixer and stir at a vacuum degree of 10 -3 Pa, mixed for 2 hours under the condition of stirring speed of 200r / min, during which time the flux was added dropwise at a dropping rate of 2mL / min; a low-temperature fast-curing solder was obtained.
[0038] The flux is composed of a thermosensitive polymer, an amphiphilic active agent, a free radical scavenger and a bio-based lubricant in a weight ratio of 9:5:2:1; Table: Components and mass ratios of raw materials in Preparation Examples 27-31 (kg)
[0039] Preparation Example 32 A low temperature fast solidifying solder, which is different from Preparation Example 27 in that the preparation method is as follows: A1. Put the multi-element alloy matrix powder and the particle dopant into a high-energy ball mill, then add anhydrous ethanol, and ball mill at a speed of 400 r / min for 4 hours to obtain a mixed material; A2: Transfer the mixture obtained in A1 into a vacuum mixer and stir at a vacuum degree of 10 -3 Pa, mixed for 2 hours under the condition of stirring speed of 200r / min, during which time the flux was added dropwise at a dropping rate of 2mL / min; a low-temperature fast-curing solder was obtained.
[0040] Preparation Example 33 A low temperature fast solidifying solder, which is different from Preparation Example 27 in that the preparation method is as follows: A1. Put the multi-element alloy matrix powder and the particle dopant into a high-energy ball mill, then add anhydrous ethanol, and ball mill at a speed of 450 r / min for 5 hours to obtain a mixed material; A2: Transfer the mixture obtained in A1 into a vacuum mixer and stir at a vacuum degree of 10-3 Pa, mixed for 2 hours under the condition of stirring speed of 200r / min, during which time the flux was added dropwise at a dropping rate of 2mL / min; a low-temperature fast-curing solder was obtained.
[0041] Preparation Example 34 A low temperature fast solidifying solder, which is different from Preparation Example 27 in that the preparation method is as follows: A1. Put the multi-element alloy matrix powder and the particle dopant into a high-energy ball mill, then add anhydrous ethanol, and ball mill at a speed of 350 r / min for 3 hours to obtain a mixed material; A2: Transfer the mixture obtained in A1 into a vacuum mixer and stir at a vacuum degree of 10 -3 Pa, mixed for 2.5 hours under the condition of stirring speed of 250r / min, during which time the flux was added dropwise at a dropping rate of 3mL / min; a low-temperature fast-curing solder was obtained.
[0042] Preparation Example 35 A low temperature fast solidifying solder, which is different from Preparation Example 27 in that the preparation method is as follows: A1. Put the multi-element alloy matrix powder and the particle dopant into a high-energy ball mill, then add anhydrous ethanol, and ball mill at a speed of 350 r / min for 3 hours to obtain a mixed material; A2: Transfer the mixture obtained in A1 into a vacuum mixer and stir at a vacuum degree of 10 -2 Pa, mixed for 3 hours under the condition of stirring speed of 300r / min, during which time the flux was added dropwise at a dropping rate of 4mL / min; a low-temperature fast-curing solder was obtained.
[0043] Preparation Example 36 A low-temperature fast-curing solder, which is different from Preparation Example 27 in that the flux is composed of a temperature-sensitive polymer, an amphiphilic activator, a free radical scavenger and a bio-based lubricant in a weight ratio of 8:6:3:2.
[0044] Preparation Example 37 A low-temperature fast-curing solder, which is different from Preparation Example 27 in that the flux is composed of a temperature-sensitive polymer, an amphiphilic activator, a free radical scavenger and a bio-based lubricant in a weight ratio of 10:4:2:1.
[0045] Preparation Examples 38-48 A low-temperature fast-curing solder, which is different from Preparation Example 27 in that the usage of the multi-alloy matrix powder used in its components is different, and the specific corresponding relationship is shown in the following table.
[0046] Table: Comparison of the usage of multi-element alloy matrix powder in preparation examples 38-48
[0047] Preparation Examples 49-61 A low-temperature fast-curing solder, which is different from Preparation Example 27 in that the usage of the multi-alloy matrix powder used in its components is different, and the specific corresponding relationship is shown in the following table.
[0048] Table: Comparison of the usage of multi-element alloy matrix powder in preparation examples 49-61
[0049] Performance testing The low-temperature fast-curing solder prepared in each embodiment was selected for testing, and the test objects were 700 portions of low-temperature fast-curing solder, 20 portions in each group; the curing temperature and curing speed thereof were tested, and the specific testing steps were as follows: Curing temperature: First, the low-temperature fast-curing solder prepared in the embodiment is sampled, and the solder sample is placed in a DSC instrument and heated at a heating rate of 5°C / min. The heat flow versus temperature curve is recorded, and the temperature corresponding to the endothermic peak on the curve is the curing temperature; the test results and evaluation criteria are as follows: Curing temperature <140°C (considered as low curing temperature); 140℃<curing temperature<180℃ (considered as normal curing temperature) Curing temperature>180℃ (considered as high curing temperature).
[0050] Curing speed: First, the low-temperature fast-curing solder prepared in the embodiment is sampled, and a visual welding monitoring platform is built, equipped with a high-speed camera, to directly capture the entire process of solder melting and curing, and record the time from the solder joint surface solidification to no longer having liquid flow characteristics, to obtain the curing time of the prepared low-temperature fast-curing solder, and characterize the curing speed of the low-temperature fast-curing solder based on this data; the test results and evaluation criteria are as follows: Curing time < 5s (considered as fast curing speed); 5s<curing time<15s (considered as normal curing speed) Curing time>15s (considered as slow curing speed).
[0051] It should be specifically explained that the low-temperature rapid solidification solder prepared above is the low-temperature rapid solidification solder produced in a normal production method, and the data of the defective low-temperature rapid solidification solder produced is discarded.
[0052] Examples 1-5 A low-temperature fast-curing solder and its corresponding preparation methods are shown in the following table.
[0053] Table: Comparison of the use of low temperature fast curing solder in Examples 1-5
[0054] The low temperature fast curing solders in the above Examples 1-5 were sampled, and their curing temperatures and curing times were tested according to the above measurement steps and measurement standards. The average values of the test results were recorded in the following table.
[0055] Table: Performance test results of curing temperature and curing time of Examples 1-5
[0056] As can be seen from the above table, the low-temperature fast-curing solder preparation processes in Examples 1-5 all have a good effect of improving the production effect of the low-temperature fast-curing solder. The addition of bismuth in the multi-element alloy matrix powder significantly reduces the melting point of the alloy, and forms a eutectic structure with tin, which changes the crystallization temperature range of the alloy, so that the solder can start the melting and solidification process at a lower temperature, providing a basic support for achieving low-temperature solidification; during the solidification process of the solder, the cerium-doped particles act as heterogeneous core adsorption atoms, which reduces the energy barrier required for nucleation of the alloy system, promotes grain refinement and uniform distribution, and numerous fine grains accelerate the solidification process and shorten the solidification time, thereby achieving the purpose of improving the production effect of the low-temperature fast-curing solder; Its curing temperature is 134.7-144.6°C, which is considered to be a low curing temperature; its curing time is 3.72-4.75s, which is considered to be a fast curing speed; It can be seen that when the production raw materials are certain, the production effect of the low-temperature fast-curing solder can be increased by adjusting the proportion of the preparation raw materials. Combined with the data in the above table, it is not difficult to see that when preparing the low-temperature fast-curing solder, 55 parts of the multi-alloy matrix powder, 15 parts of the particle dopant, 22 parts of the flux, and 4 parts of anhydrous ethanol are used, the curing temperature is the lowest. The reason for this is that the proportion of the multi-alloy matrix powder is relatively moderate, so that there are more cerium-doped particles, which act as a large number of heterogeneous cores during the solidification process, greatly reducing the energy required for alloy nucleation, so that the alloy can start crystallization at a very small degree of supercooling, significantly lowering the curing starting temperature, which is obtained from Examples 1-5.
[0057] It can be seen that when the production raw materials are certain, the production effect of the low-temperature fast-curing solder can be increased by adjusting the proportion of the prepared raw materials. Combined with the data in the above table, it is not difficult to see that when preparing the low-temperature fast-curing solder, using 60 parts of multi-alloy matrix powder, 12 parts of particle dopants, 20 parts of flux, and 3 parts of anhydrous ethanol, the curing time is the shortest. The reason for this is that 60 parts of the multi-alloy matrix powder as the main body provides sufficient metal to ensure the basic strength and conductivity required for the rapid forming of the solder joint. Its relatively simple alloy composition can flow quickly to fill the solder joint after melting, reducing the problem of slow melting due to complex components, and gaining time for subsequent rapid solidification, which is obtained from Examples 1-5.
[0058] Embodiment 6-11 A low-temperature fast-curing solder and its corresponding preparation methods are shown in the following table.
[0059] Table: Comparison of low temperature fast curing solder usage in Examples 6-11
[0060] The low-temperature fast-curing solders in the above-mentioned Examples 6-11 were sampled, and their curing temperatures and curing times were tested according to the above-mentioned measurement steps and measurement standards. The average values of the test results were recorded in the following table.
[0061] Table: Performance test results of curing temperature and curing time of Examples 1, 6-11
[0062] As can be seen from the above table, the low-temperature fast-curing solder preparation processes in Examples 6-11 all have a good effect of improving the production effect of the low-temperature fast-curing solder. The addition of bismuth in the multi-element alloy matrix powder significantly reduces the melting point of the alloy, and forms a eutectic structure with tin, which changes the crystallization temperature range of the alloy, so that the solder can start the melting and solidification process at a lower temperature, providing a basic support for achieving low-temperature solidification. During the solidification process of the solder, the cerium-doped particles act as heterogeneous core adsorption atoms, which reduces the energy barrier required for nucleation of the alloy system, promotes grain refinement and uniform distribution, and numerous fine grains accelerate the solidification process and shorten the solidification time, thereby achieving the purpose of improving the production effect of the low-temperature fast-curing solder. Its curing temperature is 136.6-139.1°C, which is considered to be a low curing temperature; its curing time is 3.51-3.91s, which is considered to be a fast curing speed; It can be seen that when the production raw materials are certain, the production effect of the low-temperature fast-curing solder can be increased by adjusting the preparation conditions. Combined with the data in the above table, it is not difficult to see that when preparing the low-temperature fast-curing solder, the ball milling speed and time in the initial mixing process are increased; the vacuum degree, flux dripping rate, stirring speed, and mixing time in the secondary mixing process are increased, and the solidification temperature is reduced and the solidification speed is accelerated. The reason is that the higher ball milling speed and longer ball milling time significantly enhance the mechanical action between the multi-element alloy matrix powder and the functional particle dopant; the nanoparticles can be more deeply and evenly embedded in the alloy matrix, as heterogeneous nucleation sites, effectively reducing the supercooling required for alloy solidification, and promoting the reduction of solidification temperature. The uniform dispersion of nanoparticles in the alloy matrix optimizes the internal structure of the solder, and the diffusion path of atoms during solidification is regular, which accelerates the solidification process; the flux dripping rate is accelerated, the stirring speed is increased, and the mixing time is extended, which can allow the flux to wrap the alloy powder more quickly and fully, shortening the solidification time, as obtained by Examples 1, 6-9.
[0063] It can be seen that when the production raw materials are certain, the production effect of low-temperature fast-curing solder can be increased by adjusting the proportion of flux raw materials. Combined with the data in the above table, it is not difficult to see that when preparing low-temperature fast-curing solder, a flux prepared by 9 parts of thermosensitive polymer, 5 parts of amphiphilic active agent, 2 parts of free radical scavenger, and 1 part of bio-based lubricant is used. The curing temperature and curing time are the shortest. The reason for this is that the content of thermosensitive polymer in this flux ratio is relatively high, and its stretched molecular chain can enhance the fluidity of the solder, and the heat transfer is more efficient, which prompts the alloy to reach the nucleation temperature faster, which is conducive to starting the solidification process at a lower temperature. The amphiphilic active agent gives full play to the interface adaptive function, quickly infiltrates the substrate to accelerate heat transfer, and melts the solder quickly; the thermosensitive polymer accurately limits the flow of solder in the high-temperature welding area to ensure rapid forming of the solder joint, which is obtained from Examples 1 and 10-11.
[0064] Examples 12-22 A low-temperature fast-curing solder and its corresponding preparation methods are shown in the following table.
[0065] Table: Comparison of the use of low temperature and fast curing solder in Examples 12-22
[0066] The low-temperature fast-curing solders in the above-mentioned Examples 12-22 were sampled, and their curing temperatures and curing times were tested according to the above-mentioned measurement steps and measurement standards. The average values of the test results were recorded in the following table.
[0067] Table: Performance test results of curing temperature and curing time of Examples 1, 12-22
[0068] As can be seen from the above table, the low-temperature fast-curing solder preparation processes in Examples 12-22 all have a good effect of improving the production effect of the low-temperature fast-curing solder. The addition of bismuth in the multi-element alloy matrix powder significantly reduces the melting point of the alloy, and forms a eutectic structure with tin, which changes the crystallization temperature range of the alloy, so that the solder can start the melting and solidification process at a lower temperature, providing a basic support for achieving low-temperature solidification. During the solidification process of the solder, the cerium-doped particles act as heterogeneous core adsorption atoms, which reduces the energy barrier required for nucleation of the alloy system, promotes grain refinement and uniform distribution, and numerous fine grains accelerate the solidification process and shorten the solidification time, thereby achieving the purpose of improving the production effect of the low-temperature fast-curing solder. Its curing temperature is 136.5-139.4°C, which is considered to be a low curing temperature; its curing time is 3.61-3.91s, which is considered to be a fast curing speed; It can be seen that when the production raw materials are certain, the production effect of the low-temperature fast-curing solder can be increased by adjusting the preparation conditions. Combined with the data in the above table, it is not difficult to see that when preparing the multi-element alloy matrix powder, it is prepared from 4 parts of tin, 4 parts of bismuth, 0.8 parts of indium, and 1.2 parts of gallium. The low-temperature fast-curing solder prepared has the lowest curing temperature. The reason for this is that the bismuth content in this ratio is as high as 40%. Bismuth, as an element that can significantly reduce the melting point of the alloy, greatly lowers the melting point of the alloy at this ratio, so that the solder can start the solidification process at a lower temperature, which is obtained from Examples 1 and 12-15.
[0069] It can be seen that when the production raw materials are certain, the production effect of the low-temperature fast-curing solder can be increased by adjusting the preparation conditions. Combined with the data in the above table, it is not difficult to see that when preparing the multi-alloy matrix powder, it is prepared from 5 parts of tin, 3 parts of bismuth, 1 part of indium, and 1 part of gallium. The low-temperature fast-curing solder prepared by it has the fastest curing speed. The reason for this is that 50% tin ensures good fluidity, 30% bismuth reduces the melting point so that the solder can melt and solidify quickly, 10% indium is conducive to solder joint formation, and 10% gallium forms a microscopic low melting point area, which promotes the overall solder to flow and solidify quickly at low temperatures, which is obtained from Examples 1 and 12-15.
[0070] It can be seen that when the production raw materials are certain, the production effect of low-temperature fast-curing solder can be increased by adjusting the preparation conditions. Combined with the data in the above table, it is not difficult to see that when preparing multi-element alloy matrix powder, increasing the vacuum degree, melting temperature, melting time in the smelting process, the ultrasonic frequency and atomizing gas flow rate in the atomization process, and the speed of the grading wheel in the airflow classification process, the solidification temperature is reduced and the solidification speed is accelerated. The reason for this is that when the smelting vacuum degree is increased, the atomic arrangement is more regular when the alloy solidifies, and the heat transfer barrier is continuously reduced, which further optimizes the stability of the solidification temperature and the melting temperature. The fusion of alloy elements will be more complete and thorough, high temperature will promote the full mixing of atoms of different elements, the melting points of various parts will be closer during solidification, the solidification temperature consistency is excellent, the ultrasonic frequency is increased to make the uniformity of powder particle size distribution approach the extreme, almost in an ideal state of monodisperse, and the ideal liquid temperature is reached at the moment of melting; the atomizing gas flow rate is increased, and the high-speed atomizing gas promotes the rapid cooling of alloy droplets, and the powder particles have a very high degree of grain refinement; the high-speed rotating grading wheel can accurately screen out the multi-element alloy matrix powder that meets the requirements, and further optimize the uniformity of powder particle size, which is obtained by Examples 1 and 16-22.
[0071] Examples 23-35 A low-temperature fast-curing solder and its corresponding preparation methods are shown in the following table.
[0072] Table: Comparison of the use of low temperature and fast curing solder in Examples 23-35
[0073] The low-temperature fast-curing solders in the above-mentioned Examples 23-35 were selected, and their curing temperatures and curing times were tested according to the above-mentioned measurement steps and measurement standards. The average values of the test results were recorded in the following table.
[0074] Table: Performance test results of curing temperature and curing time of Examples 1, 23-35
[0075] As can be seen from the above table, the low-temperature fast-curing solder preparation processes in Examples 23-35 all have a good effect of improving the production effect of the low-temperature fast-curing solder. The addition of bismuth in the multi-element alloy matrix powder significantly reduces the melting point of the alloy, and forms a eutectic structure with tin, which changes the crystallization temperature range of the alloy, so that the solder can start the melting and solidification process at a lower temperature, providing a basic support for achieving low-temperature solidification. During the solidification process of the solder, the cerium-doped particles act as heterogeneous core adsorption atoms, which reduces the energy barrier required for nucleation of the alloy system, promotes grain refinement and uniform distribution, and numerous fine grains accelerate the solidification process and shorten the solidification time, thereby achieving the purpose of improving the production effect of the low-temperature fast-curing solder. Its curing temperature is 136.2-139.1°C, which is considered to be a low curing temperature; its curing time is 3.59-3.83s, which is considered to be a fast curing speed; It can be seen that when the production raw materials are certain, the production effect of the low-temperature fast-curing solder can be increased by adjusting the preparation conditions. Combined with the data in the above table, it is not difficult to see that when preparing the particle dopant, it is prepared from 4 parts of cerium-doped particles, 2 parts of silver-doped particles, and 4 parts of carbon-doped dispersion. The low-temperature fast-curing solder prepared by it has the lowest curing temperature and the fastest curing speed. The reason for this is that the cerium-doped particle content is the highest, which is 40%; the cerium-doped particles can be used as heterogeneous core adsorption atoms during the solidification process, which can effectively reduce the energy barrier required for nucleation of the alloy system, promote grain refinement and uniform distribution, and numerous fine grains accelerate the solidification process and also reduce the solidification temperature; the alloy can start solidification at a lower degree of supercooling. Due to the high content of cerium-doped particles, the grain refinement and uniform distribution can be promoted. The solidification process starts simultaneously from numerous fine nuclei, which greatly shortens the solidification time, as obtained from Examples 1 and 23-26.
[0076] It can be seen that when the production raw materials are certain, the production effect of low-temperature fast-curing solder can be increased by adjusting the preparation conditions. Combined with the data in the above table, it is not difficult to see that when preparing multi-element alloy matrix powder, increasing the reaction temperature and time in the preparation process of cerium-doped particles, the heating temperature, stirring speed, reaction time in the preparation process of silver-doped particles, and the ultrasonic oscillation frequency and time in the preparation process of carbon-doped dispersion, the prepared low-temperature fast-curing solder has a lower curing temperature and a higher curing speed. The reason for this is that after the temperature is increased and the time is extended, the crystallization process of cerium-doped particles is more perfect, the generated particle size is more uniform, the particle size distribution range is narrowed, and the crystallization is good. When the cerium-doped particles are mixed with the multi-element alloy matrix powder, they can be integrated into it more quickly to activate the solidification activity of the alloy; the heating temperature is increased, the stirring is accelerated and the reaction time is extended, so that the silver nitrate reduction reaction is more fully carried out, and the generated silver-doped particles have a smaller particle size and a higher purity; when mixed with other components, the small-size silver-doped particles can be quickly dispersed and synergistically activate the activity of the material; higher-frequency ultrasonic oscillation and longer treatment make the carbon nanotubes dispersed in the dispersion liquid almost perfectly and in a monodisperse state; after the solder is melted, the extremely dispersed carbon nanotubes quickly transfer heat, stimulate atomic thermal motion, and provide strong power for solidification, as obtained by Examples 1 and 27-32.
[0077] It can be seen that when the production raw materials are certain, the production effect of the low-temperature fast-curing solder can be increased by adjusting the preparation conditions. Combined with the data in the above table, it is not difficult to see that when preparing the multi-alloy matrix powder, the mass ratio of cerium nitrate to polyvinyl pyrrolidone is 5:1; the mol ratio of silver nitrate to glucose is 1:1; the mass ratio of carbon nanotubes to sodium dodecyl sulfate is 1:0.08, and the prepared fast-curing solder has the lowest curing temperature and the fastest curing speed, which is obtained from Examples 1 and 33-35.
[0078] This specific embodiment is only an explanation of the present invention, not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of the claims of the present invention, it is protected by the patent law.
Claims
1. A method for preparing a low-temperature fast-curing solder, characterized in that: The following steps are involved: A1. Put the multi-element alloy matrix powder and the particle dopant into a high-energy ball mill, then add anhydrous ethanol, and ball mill at a speed of 350-450 r / min for 3-5 hours to obtain a mixed material; A2, transfer the mixture obtained in A1 into a vacuum mixer, mix for 2-3 hours at a vacuum degree of 10-3Pa and a stirring speed of 200-300r / min, during which time the flux is added dropwise at a dropping rate of 2-4mL / min; A low temperature fast solidifying solder is obtained.
2. The method for preparing a low-temperature rapid solidification solder according to claim 1, characterized in that: The components and weight proportions of the raw materials for preparing the low-temperature rapid curing solder are as follows: 55-62 parts of multi-element alloy matrix powder, 10-15 parts of particle doping agent, 3-4 parts of anhydrous ethanol and 18-22 parts of soldering flux.
3. A method for preparing a low-temperature fast-curing solder according to claim 1, characterized in that: The multi-element alloy matrix powder is prepared from tin, bismuth, indium and gallium; and the preparation method thereof comprises the following steps: C1. Place 99% pure tin, bismuth, indium and gallium metal blocks into a vacuum induction melting furnace at a vacuum degree of 10 -5 -10 -4 Pa, smelting at 1100-1300℃ for 30-45min to obtain multi-element alloy liquid; C2, placing the multi-component alloy liquid obtained in C1 in the atomizing chamber of an ultrasonic atomizing device, atomizing the alloy liquid into tiny droplets at an ultrasonic frequency of 20-30kHz and an atomizing gas argon flow rate of 12-18L / min, cooling and solidifying the droplets through circulating water at a temperature of 10°C and a flow rate of 0.5L / min during the drop, to obtain a multi-component alloy powder; C3. The multi-component alloy powder obtained in C2 is transferred to an air flow classifier, and air flow classification is performed under the conditions of a classifying wheel speed of 1500-2000 r / min, an air flow rate of 8 m³ / h, and an air flow pressure maintained at 0.2 MPa to obtain a multi-component alloy matrix powder.
4. The method for preparing a low-temperature rapid curing solder according to claim 1, characterized in that: The components and weight proportions of the raw materials for preparing the multi-element alloy matrix powder are as follows: Tin 3.5-5.5 parts, bismuth 2.5-4 parts, indium 0.8-1.5 parts and gallium 0.8-1.5 parts.
5. A low temperature fast curing solder formula according to claim 1, characterized in that: The particle dopant is prepared from cerium-doped particles, silver-doped particles and carbon-doped dispersion; and the preparation method thereof comprises the following steps: B1. Dissolve cerium nitrate in 4 times the volume of ethylene glycol solution, then add polyvinyl pyrrolidone and continue stirring for 30 minutes, then place in a high-pressure reactor, react at a temperature of 180-200°C for 4-6 hours. After the reaction is completed, wait for the high-pressure reactor to cool naturally to room temperature, transfer the generated precipitate to a centrifuge tube, centrifuge at a speed of 8000r / min for 15 minutes, take the precipitate, then add anhydrous ethanol to the precipitate, use an oscillator to oscillate for 5 minutes, and then centrifuge again under the same conditions. Repeat 3 times and heat at a temperature of 60°C and a vacuum degree of 10 -4 The cerium-doped particles were obtained by drying under Pa conditions for 12 h; B2. Add 5 times the volume of glucose solution to the silver nitrate solution, stir at 300-400 r / min, 80-100°C for 2-3 h, then transfer the product to a centrifuge tube, add 5 times the volume of anhydrous ethanol, oscillate for 5 min, then centrifuge at 8000 r / min for 10 min, remove the supernatant, repeat 3 times, and heat at 60°C in a vacuum for 10 min. - 4 Drying under Pa conditions for 12 h yields silver-doped particles; B3, adding carbon nanotubes to sodium dodecyl sulfate, then placing in 10 times the volume of water, ultrasonically oscillating at an ultrasonic frequency of 40-60 Hz for 30-45 minutes, taking out the dispersion to obtain a carbon-doped dispersion; B4, the cerium-doped particles obtained in B1, the silver-doped particles obtained in B2, and the carbon-doped dispersion obtained in B3 were mixed, and then placed in 1 volume of anhydrous ethanol, followed by ultrasonic cleaning at a frequency of 30 Hz for 10 min, and then vacuumed to 10 -4 Pa, and dried at 60°C for 6h to obtain a particle dopant.
6. The method for preparing a low-temperature rapid solidification solder according to claim 1, characterized in that: The components and weight proportions of the raw materials for preparing the particle dopant are as follows: 2-4 parts of cerium-doped particles, 2-5 parts of silver-doped particles and 3-4 parts of carbon-doped dispersion.
7. The method for preparing a low-temperature rapid solidification solder according to claim 1, characterized in that: The soldering flux is composed of a thermosensitive polymer, an amphiphilic active agent, a free radical scavenger and a bio-based lubricant in a weight ratio of (8-10): (4-6): (2-3): (1-2).
8. The method for preparing a low-temperature rapid solidification solder according to claim 5, characterized in that: The mass ratio of cerium nitrate to polyvinyl pyrrolidone in B1 is (5-10): 1; The molar ratio of silver nitrate to glucose in B2 is 1:(1-1.5); The mass ratio of carbon nanotubes to sodium dodecyl sulfate in B3 is 1:(0.08-0.12).
9. A low-temperature fast-curing solder prepared according to the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Lead-free alloy for low-temperature welding welder
CN101537545A
Low-temperature tin alloy and preparation method thereof
CN106244851A
Electronic component welding indium-containing solder
CN108213765A
Low-temperature lead-free solder
CN108971793A
Low-temperature environment-friendly multi-element alloy solder paste and preparation method thereof
CN111590241A